[an error occurred while processing this directive]

Quadratic Equations - Exercise 3 - Extracting Square Roots

Fill in the missing justifications for steps below where the equation  (2x + 1)2 - 3 = 26 is solved
with solutions x = (-1 +/- 29)/2.
 

STATEMENT JUSTIFICATION
(2x + 1)2 - 3 = 26

(2x + 1)2  = 29

2x + 1 = +/-  29

2x = -1 +/-  29

x = (-1 +/-  29) / 2

 

Given

____________________________

Extract Square Roots

_______________________________

_______________________________

 

 

[an error occurred while processing this directive]